0.8 nm single wall carbon nanotubes for wideband ultrafast pulse generation. (8th March 2016) - Kang, Z; Xu, Y; Jia, Z X; Qin, G S; Qin, W P
Abstract: We demonstrate wideband ultrafast optical pulse generation at 1, 1.56 and 2 μ m by using single polymer composite saturable absorber (SA) based on 0.8 nm single wall carbon nanotubes (SWCNTs). The SWCNTs were mixed with sodium carboxymethylcellulose (NaCMC) to form SWCNT SA films. The film then integrated into ytterbium-(Yb-), erbium-(Er-) and thulium-(Tm-) doped ring fiber laser cavities. Using this film, we achieve 380 ps, 830 fs, and 1.24 ps mode-locked pulses at 1035, 1560, and 1933 nm, respectively. These results suggest that 0.8 nm SWCNTs are potentially useful as optical elements in wideband fiber lasers.